FAKTOR-FAKTOR YANG MENGHAMBAT TUMBUH DAN BERKEMBANGNYA BADAN USAHA MILIK DESA DI DESA PEMATANG TEBIH KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2014-2015 - Mayu, Welli Indra; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted with the aim to determine the factors that hinder the growth and development of village-owned enterprises in Causeway Village tebih Ujung Batu District of Rokan Hulu years 2014-2015 were reviewed based on growth indicators Owned tebih Desa Mandiri years 2014-2015. The main problem in this study is not the development of village-owned enterprises tebih Mandiri while village-owned enterprises tebih Mandiri has the potential of natural resources that can be developed to increase revenue and economic growth Village. The theory used in this research is the theory of village-owned enterprises, and the factors that hinder the growth and development of village-owned enterprises. This research uses descriptive analysis method using a qualitative approach. This study using purposive sampling and snowball sampling that interview with the informant as the object information that aims to achieve the goal. Data collection techniques used in this study was observational, a note of Field, documentation and interviews with informants research. Village-owned enterprises, hereinafter referred to BUMDes is an institution or agency The village economy is formed and owned by the village government, professionally managed with capital wholly or largely a village separated wealth. Village-owned enterprises tebih Mandiri is one of the village -owned enterprises which are in Sub Ujung Batu Rokan Hulu standing on date 10 November 2013. Owned Desa Mandiri tebih until now only engaged in the financial business, namely savings and loans, while the village-owned enterprises tebih Mandiri has sufficient resource potential support for development. As for the factors that hinder the growth and development of village-owned enterprises tebih Mandiri include (a) Lack of knowledge of administrators in understanding the meaning of leadership, managerial and governance of village-owned enterprises with the lack of experience of a director in entrepreneurship weeks to manage a business organization, (b) not relations research agreement with any party because the village-owned enterprises is only running one business unit, (c) Owned Rural tebih Self is not born out of the spirit of emancipation local, (d) the absence of tradition berdesa strong due to a lack of solidarity, cooperation and mutual cooperation between the villagers and (e) does not get full support from the Village supra. Keyword :The village government, village-owned enterprises, an inhibiting factor.